The Calculation and Analysis of the Bistatic Quantum Radar Cross Section for the Typical 2-D Plate - Chonghua Fang; Hui Tan; Qi-Feng Liu; Li Tao; Long Xiao; Yanjun Chen; Liang Hua (IEEE Photonics Journal, 2018)
The quantum radar cross section (QRCS) describes how much return one gets when illuminating an object with a handful of photons. However, the previous studies mainly focused on the monostatic scattering of quantum radar. In this study, in response to the four key questions raised by ourselves in bistatic quantum radar cross section (BIQRCS), we calculate and analyze the BIQRCS for the typical tow-dimensional plate. First, as mentioned by Brandsema, the further derived analytical solution for the rectangular plate is obtained. In addition, the influence of incident frequency and the number of photons on the BIQRCS for the plate were obtained. Besides, we first reveal that the envelope curves of sidelobes in BIQRCS at the given incidence display the invariance in frequency. Finally, we show some comparison results among the BIQRCS, classical radar cross section (CRCS), and monostatic QRCS for the plate and find the advantage of sidelobe of the BIQRCS in given direction. We anticipate that these research results will find use in the detection and discrimination of stealthy platforms.